1989
DOI: 10.3109/00048678909062145
|View full text |Cite
|
Sign up to set email alerts
|

Low Plasma β-Endorphin in Post-Traumatic Stress Disorder

Abstract: We compared serum cortisol, ACTH and plasma beta-endorphin in 21 Post-Traumatic Stress Disorder patients and 20 controls. Although we found no important disturbance in diurnal rhythms, the PTSD patients had significantly higher A.M. serum cortisols compared with controls. Both A.M. and P.M. plasma beta-endorphins in PTSD patients were significantly lower compared with controls. These data suggest that plasma beta-endorphin may be a marker for PTSD and that chronic endogenous opioid depletion may play a role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Few studies have examined levels of endogenous opioids in PTSD patients. Studies examining ß-endorphin levels have been conflicting with lower [76], comparable [97], and higher levels [98] being reported in PTSD patients compared to controls. In response to exercise-induced stress, PTSD patients were found to have an increased ß-endorphin response in one study [97], while another study found a negative correlation between ß-endorphin levels and avoidant and intrusive symptoms in PTSD patients.…”
Section: Regulation Of the Lc During Stressmentioning
confidence: 99%
“…Few studies have examined levels of endogenous opioids in PTSD patients. Studies examining ß-endorphin levels have been conflicting with lower [76], comparable [97], and higher levels [98] being reported in PTSD patients compared to controls. In response to exercise-induced stress, PTSD patients were found to have an increased ß-endorphin response in one study [97], while another study found a negative correlation between ß-endorphin levels and avoidant and intrusive symptoms in PTSD patients.…”
Section: Regulation Of the Lc During Stressmentioning
confidence: 99%
“…Of particular relevance to the present study, HPA dysregulation has been reported in PTSD, although the exact nature of the dysregulation remains a matter of debate. Some studies have shown elevated basal urinary and plasma cortisol levels in PTSD patients compared to controls (Hoffman et al, 1989;, while others have shown lower urinary and plasma cortisol Yehuda et al, 1990Yehuda et al, , 1993Yehuda et al, , 1995. Again, discrepancies may be related to the nature or duration of the trauma, or to the expression of specific symptoms (de Quervain et al, 2009;Handwerger, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The mPFC, particularly the infralimbic cortex, is a key region involved in extinction learning (Milad and Quirk, 2002;Quirk et al, 2000;. Furthermore, humans with PTSD display dysregulated hypothalamicepituitaryeadrenal (HPA) axis activity, although the nature of this dysregulation remains unclear Hoffman et al, 1989;Yehuda et al, 1995Yehuda et al, , 1993Yehuda et al, , 1990.…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 99%
“…For these reasons, the relations of beta-endorphin with traumas and related disorders are also examined, post-traumatic stress disorder (PTSD) among them (Merenlender-Wagner et al, 2009). Hoffman et al (1989) propose plasma β-endorphin as a marker for PTSD after finding the hormone diurnal levels to be significantly lower than in controls. Although traumas are not explicitly included in the diagnosis of any type of depression as they are in PTSD, trauma history is a factor in etiology of depression.…”
Section: Introductionmentioning
confidence: 95%